ChemInform Abstract: An Electrophilic Hypervalent Iodine Reagent for Trifluoromethylthiolation. Issue 31 (11th July 2013) - Shao, Xinxin; Wang, Xueqiang; Yang, Tao; Lu, Long; Shen, Qilong
Abstract The air‐ and moisture‐stable reagent (I) allows the direct transfer of the ‐S‐CF3 group to different classes of substrates such as β‐ketoesters, boronic acids, alkynes, and aldehydes under mild conditions.